PERAN SUPERVISI KEPALA SEKOLAH TERHADAP PELAKSANAAN TUGAS POKOK GURU DI SMPN 7 KOTA BOGOR - Siti Djumhurijah (Universitas Pakuan, 2021)
THE ROLE OF SCHOOL PRINCIPAL SUPERVISION AGAINST THE IMPLEMENTATION OF PRIMARY DUTIES OF TEACHERS IN JUNIOR HIGH SCHOOLS (SMPN 7 KOTA BOGOR)This research is a school action research which aims to reveal the role of principal supervision on the implementation of the main duties of the teacher in planning, implementing and evaluating the learning process. This study uses an Action Research Approach. The results of this study indicate the results of the supervision carried out by the principal can improve the implementation of the main duties of teachers at SMP Negeri 7 Bogor City. This also proves that the supervision of the principal and individual meetings with each teacher to reflect on the learning process has a very important role in improving the implementation of teacher main tasks. The implication of this research is that if the role of principal supervision is always carried out, the learning process in the classroom will provide good feedback between teachers and students.